Interventional radiological therapies in colorectal hepatic metastases - Vulasala, Sai Swarupa R.; Sutphin, Patrick D.; Kethu, Samira; Onteddu, Nirmal K.; Kalva, Sanjeeva P. (Frontiers in Oncology, 2023)
Colorectal malignancy is the third most common cancer and one of the prevalent causes of death globally. Around 20-25% of patients present with metastases at the time of diagnosis, and 50-60% of patients develop metastases in due course of the disease. Liver, followed by lung and lymph nodes, are the most common sites of colorectal cancer metastases. In such patients, the 5-year survival rate is approximately 19.2%. Although surgical resection is the primary mode of managing colorectal cancer metastases, only 10-25% of patients are competent for curative therapy. Hepatic insufficiency may be the aftermath of extensive surgical hepatectomy. Hence formal assessment of future liver remnant volume (FLR) is imperative prior to surgery to prevent hepatic failure. The evolution of minimally invasive interventional radiological techniques has enhanced the treatment algorithm of patients with colorectal cancer metastases. Studies have demonstrated that these techniques may address the limitations of curative resection, such as insufficient FLR, bi-lobar disease, and patients at higher risk for surgery. This review focuses on curative and palliative role through procedures including portal vein embolization, radioembolization, and ablation. Alongside, we deliberate various studies on conventional chemoembolization and chemoembolization with irinotecan-loaded drug-eluting beads. The radioembolization with Yttrium-90 microspheres has evolved as salvage therapy in surgically unresectable and chemo-resistant metastases.